43 EXPLORING STAFF PERCEPTIONS AND ATTITUDES TO CARE AND CAREBOTS: THE CASE OF AN ORIGINAL AIR-DISINFECTION ROBOT IN IRELAND. (25th October 2022) - Kodate, N; Kohli, P; McGinn, C; Scott, R; Ross, E; Treusch, P; Maeda, Y; Donnelly, S; Leonard, C; Cogan, L; Mannan, H; O'Shea, D; et al.
Abstract: Background: The pandemic heightened the sense of security and safety in care settings, with cleanliness and infection control becoming an even more important aspect of care delivery. Although the impact of new welfare technology on health and social care has been discussed in recent years, few studies have reported the implementation processes or human-robot interactions in care facilities in different cultural settings. The aims of this interdisciplinary research therefore were to understand needs and aspects that have to be considered for implementing an assistive robot, and to explore user perceptions, and the process by which the robots are adopted in Ireland and Japan. Methods: An original air-disinfection robot (V-Air) was developed by Akara Robotics, as part of research project "Harmonisation towards the establishment of Person-centred, Robotics-aided Care System" (Toyota Foundation, D18-ST-0005). Prior to its instalment in a rehabilitation centre in Dublin, semi-structured interviews were conducted, and observations carried out with seven care professionals, as they interacted with V-Air. The robot was then trialled for eight weeks (March-May 2022) in selected areas of the facility. After four weeks, the users filled out the System Usability Score and were asked questions at the end of the trial. Their scores and answers to the questions revealed staff perceptions and attitudes to care robots. Results: Overall, the users had positive perceptions of V-Air and its usability. Initial differences existed in staff's confidence levels, depending on prior experiences with technologies. Collective sensemaking was observed, particularly, around care delivery processes and robot functionalities. The adoption process was facilitated by several factors such as the timing of introduction, user-centred design, concept of care and organisational support. Conclusion: The findings suggest that the introduction of care robots in care settings can offer an additional layer of organisational safety, while highlighting the significance of the iterative process in adopting assistive technologies.